Analisis Strategi Customer Relationship Management (CRM) untuk Meningkatkan Kepuasan Pelayanan di Rumah Sakit Darmo Surabaya - Neny Haryuningtias; Komarun Zaman (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the implementation of Customer Relationship Management (CRM) strategies in improving patient service satisfaction at Darmo Hospital Surabaya. The competition among premium private hospitals in major cities has become increasingly intense, particularly in serving middle-to-upper-class patients with high expectations of healthcare services. This research applied a qualitative field study approach, including direct observation, interviews with patients and medical staff, and document analysis. The findings reveal that patient satisfaction improved significantly through the implementation of a comprehensive CRM strategy. The strategy emphasizes Service Excellence, which consists of six main pillars: competence, attitude, appearance, attention, action, and accountability of healthcare staff. In addition, Darmo Hospital actively strengthens long-term relationships with the community through social service programs, health seminars, and the use of digital media such as Instagram and its official website to expand interactions with patients. Patient complaints are handled promptly and efficiently through standardized procedures (SOP Handling Complaint), contributing to higher trust and loyalty among patients. Another crucial factor is healthy communication between medical staff and patients, characterized by empathy, openness, support, and personalized care. This study concludes that structured, innovative, and responsive CRM practices can enhance patient satisfaction while simultaneously strengthening the hospital’s competitive position. These findings are expected to serve as a strategic model for other hospitals aiming to improve service quality and patient loyalty in the era of global healthcare competition.